The use of mouthwash containing essential oils (LISTERINE®) to improve oral health: A systematic review - Fahad Ali Alshehri (Elsevier, 2018)
Background: Standard recommendations to maintain daily oral hygiene include tooth brushing and interdental cleaning. Evidence from literature indicates that using a mouthrinse as an adjunct provides benefit beyond mechanical methods. The objective of this article was to evaluate the short- and long-term effect of a mouthwash containing essential oils (LISTERINE®) in improving oral health. Methods: PubMed (MEDLINE) and bibliographies from the relevant retrieved reviews were searched to identify clinical studies involving the use of LISTERINE mouthrinse. The primary outcome measure was short- and long-term efficacy of mouthrinse containing essential oil (LISTERINE®) in improving oral health. Results: Based on our search, 26 studies supported the use of essential-oil-containing mouthrinse (LISTERINE®) as an adjunct to daily oral health regimen. Most studies were conducted in healthy subjects, 2 studies in orthodontic patients, 1 each in xerostomia patients and mentally disabled patients. Of these, 13 studies supported the short-term (<3 months) and 13 studies supported the long-term (3-6 months) efficacy of LISTERINE mouthrinse as an adjunct to mechanical methods. Conclusions: This review provides strong evidence of the anti-plaque and anti-gingivitis effects of essential-oil-containing mouthrinse LISTERINE® as an adjunct to daily tooth brushing and interdental cleaning. Keywords: Listerine, Mouthwash, Mouthrinse, Essential oils, Short-term efficacy, Long-term efficacy, Review